The mediating role of environmental management accounting in the relationship between strategy and environmental performance - Trịnh Hữu Lực; Lê Huỳnh Như (Tạp chí Khoa học Đại học Mở Thành phố Hồ Chí Minh - Kinh tế và Quản trị kinh doanh, 2024)
The study examines the mediating role of Environmental Management Accounting (EMA) in the relationship between Environmental Strategy (ES) and Environmental Performance (EP). The SEM structural model was used to test the hypothesis. Research results indicate that ES impacts EP, in which EMA is an intermediary. This result promotes enterprises to have a more reasonable resource allocation for strategic human resource training and to invest in an accounting information system for sustainable development, especially in developing countries like Vietnam.